Community Empowerment Through Non-Formal Education: An Analysis of Community Service Programs in Village A - Solehuddin, Moh; Faliza, Nur; Fahrizal, Effan; Heriyana, Heriyana; Yani, Ahmad (PT Inovasi Pratama Internasional, 2025)
This qualitative study examines the impact of non-formal education (NFE) in empowering rural communities by analyzing a community service program in Village A, Indonesia. Using in-depth interviews, participant observation, and documentation, the research explores how NFE initiatives-such as vocational training, literacy classes, and entrepreneurship workshops-contribute to community development. Findings indicate that NFE programs significantly enhance participants’ skills, economic independence, and social cohesion. Women and youth, in particular, benefit from increased opportunities for self-employment and active participation in community affairs. The study also identifies several challenges, including limited resources, insufficient facilitator capacity, and fluctuating motivation among participants, which hinder program sustainability. Despite these obstacles, the research highlights the importance of participatory approaches, local relevance, and strong collaboration between facilitators and community members in achieving empowerment outcomes. The integration of local wisdom and the potential use of digital tools are suggested as strategies to improve program adaptability and reach. Overall, this study concludes that non-formal education, when contextually tailored and well-facilitated, plays a vital role in fostering sustainable community empowerment in rural Indonesia. Recommendations include enhancing resource allocation, investing in facilitator training, and leveraging technology to support and expand NFE initiatives. This research contributes to the understanding of effective community empowerment strategies and provides practical insights for policymakers, educators, and development practitioners working in similar contexts.